Risk Assessment of Solid Bulk Cargo Liquefaction Consequences in Maritime Transportation under a Fuzzy Bayesian Network Approach - Muhammet Aydın (Journal of Transportation and Logistics)
Solid bulk cargo liquefaction is hazardous for bulk carrier ships as they reduce the stability of the ship. Most dry bulk ship owners face solid bulk cargo liquefaction during the carriage of ore cargoes. The consequences of cargo liquefaction could have catastrophic effects such as the ship sinking or capsizing. To improve the process of safety during the shipment of bulk cargo and reduce potential consequences, a detailed risk analysis is needed. The purpose of this paper is to conduct a systematic probabilistic risk analysis of the liquefaction of solid bulk cargo in the marine sector in order to allay this concern in order to deal with complex causation and uncertainty resulting from complex interdependence among risk factors, limited data, and a complex environment. A Bayesian network (BN) method under fuzzy logic has been utilized in the research. Whilst the BN enables us to calculate the conditional probability of each basic event in the graph, the fuzzy logic tackles uncertainty and the vagueness of expert judgment. The findings of the paper will assist solid bulk cargo owners and shippers in reducing the risk of solid bulk cargo liquefaction during maritime transportation.